Penentuan titik potong skor sindroma metabolik remaja dan penilaian validitas diagnostik parameter antropometri: analisis Riskesdas 2013 - Zahra Anggita Pratiwi; Mubasysyir Hasanbasri; Emy Huriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: The risk of death caused by non-communicable diseases is related to metabolic syndrome. Metabolic syndrome not only occurs in adults, but also occurs in adolescents. The problem of metabolic syndrome in adolescents shows the importance of early detection and management. Early detection of metabolic syndrome in adolescents can be done through non-invasive approaches such as anthropometric measurements. However, the definition of metabolic syndrome has so far not reached an agreement.Objective: This study aims 1) To know the intersection points of adolescent metabolic syndrome 2) To know the best anthropometry parameters for detecting metabolic syndrome in adolescents.Method: This study used cross sectional design, using Riskesdas 2013 survey data. The sample size of this study was 3273 adolescents aged 15-24 years. The analysis using receiver operating characteristic curve (ROC) indicated the accuracy of the score to diagnose metabolic syndrome, supported by area under the curve (AUC) results. The best parameters were seen from the largest AUC values, taking into account the sensitivity and specificity values.Results: The metabolic syndrome scores in general for Indonesian adolescents=2.21 (sensitivity=83%, specificity=84%). Specific cutoff point for women=2.02 (sensitivity=84%, specificity=85%), and for males=2.40 (sensitivity=86%, specificity=82%). The best anthropometric parameters for detecting metabolic syndrome in adolescents are abdominal circumference (AUC=0.77; sensitivity=71%, specificity=67%).Conclusion: Abdominal circumference has the best validity and can be used for early detection of the risk of metabolic syndrome in adolescents